Corrosion-resistant thermal insulation composite material and preparation method thereof
By introducing modified inorganic fillers and optimizing the polyurethane resin formula, the problem of insufficient corrosion resistance of existing corrosion-resistant insulation materials in harsh environments is solved, and the double improvement of corrosion resistance and insulation performance of composite materials is achieved.
Patent Information
- Application Number
- CN202510322619.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing corrosion-resistant insulation materials are difficult to meet corrosion resistance requirements in harsh environments, and the preparation process is complex, costly or unstable.
By introducing specific modified inorganic fillers, the ratio of polyurethane resin to diphenylmethane diisocyanate is optimized, and the temperature, time and rotation speed in the preparation process are finely adjusted and controlled to improve the mechanical properties and corrosion resistance of the composite material.
The double improvement of composite materials has been achieved, which not only improves corrosion resistance but also enhances thermal insulation performance, and has simplified process, reduced costs and stable performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane materials and relates to a corrosion-resistant heat-insulating composite material and a preparation method thereof. Background Art
[0002] In industrial production and daily life, corrosion-resistant thermal insulation materials are widely used due to their unique properties. Traditional thermal insulation materials often cannot meet the corrosion resistance requirements in harsh environments, such as strong acid, strong alkali or high temperature and high humidity environments, which limits their application scope. Therefore, it is particularly important to develop a composite material that has both good thermal insulation performance and excellent corrosion resistance.
[0003] At present, most corrosion-resistant insulation materials on the market use a composite method of organic and inorganic materials to improve the overall performance of the materials. However, many existing composite materials have problems such as complex processes, high costs or unstable performance during the preparation process. For example, some composite materials have poor compatibility between inorganic fillers and organic matrices, resulting in reduced mechanical properties of the materials; other composite materials fail to achieve the expected corrosion resistance due to improper addition of corrosion-resistant components.
[0004] The present invention provides a corrosion-resistant thermal insulation composite material and a preparation method thereof. The composite material achieves a dual improvement in corrosion resistance and thermal insulation performance by optimizing the formula and preparation process. Specifically, the present invention enhances the interaction between the organic matrix and the inorganic filler by introducing a specific modified inorganic filler, thereby improving the overall mechanical properties and corrosion resistance of the composite material. At the same time, by finely controlling various parameters in the preparation process, such as temperature, time, rotation speed, etc., the performance stability and preparation efficiency of the composite material are ensured. Summary of the invention
[0005] The purpose of the present invention is to provide a corrosion-resistant heat-insulating composite material and a preparation method thereof, which has the characteristics of corrosion resistance and heat insulation.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A corrosion-resistant thermal insulation composite material, wherein the corrosion-resistant thermal insulation composite material has the following formula: by weight, 80-100 parts of polyurethane resin, 30-40 parts of diphenylmethane diisocyanate, 20-30 parts of modified inorganic filler, 3-5 parts of polyacrylamide, and 1-2 parts of polyvinyl alcohol. The preparation method of the modified inorganic filler is as follows: S1.1: Sodium silicate is dissolved in deionized water to obtain a sodium silicate aqueous solution with a mass fraction of 20-30%, and lithopone is dispersed in the sodium silicate aqueous solution with a solid-liquid mass ratio of 1:1. The mixture is put into a homogenizer and homogenized at 3-5 MPa for 20-30 min to obtain a mixture A; S1.2: bismuth vanadate and oxalic acid monohydrate were mixed in a mass ratio of 1:(0.5-1), and ground in a ball mill at a speed of 400 r / min for 0.5 h to obtain a mixture B; S1.3: Mix mixture B and mixture A in a mass ratio of 1:(1-2), stir at a speed of 300 r / min for 0.5 h, heat from room temperature to 300 °C and roast for 2 h. After roasting, slowly cool to room temperature, crush and grind to obtain mixture C; S1.4: Soak the rock wool fiber in deionized water at 70°C for 4 to 6 hours. After soaking, dry it at 110°C for 12 hours in a high-purity nitrogen atmosphere to obtain dry rock wool fiber. Mix the dried rock wool fiber and mixture C in a mass ratio of 1:1, put them into a ball mill for grinding, and obtain the modified inorganic filler after sufficient grinding.
[0007] Furthermore, the particle size of the mixture B in S1.2 is 600 mesh.
[0008] Furthermore, the rate of heating from room temperature to 300° C. in S1.3 is 5° C. / min.
[0009] Furthermore, the slow cooling rate in S1.3 is 2°C / min.
[0010] Furthermore, the particle size of the mixture C in S1.3 is 800 mesh.
[0011] Furthermore, the purity of the high-purity nitrogen in S1.4 is 99.99%.
[0012] Furthermore, in S1.4, the grinding machine speed is 500 r / min, and the grinding time is 1-2 h.
[0013] Furthermore, the particle size of the modified inorganic filler obtained by grinding in S1.4 is 1000 mesh.
[0014] A method for preparing a corrosion-resistant thermal insulation composite material, the method for preparing the composite material is as follows: S9.1: Heat the polyurethane to 165-175°C to make the polyurethane molten, add diphenylmethane diisocyanate in proportion, mix and stir at a speed of 200 r / min for 10-20 min to obtain a mixture D; S9.2: Add the modified inorganic filler to the mixture D, increase the stirring speed to 300 r / min, and stir for 20 to 30 min to obtain a mixture E; S9.3: Add polyacrylamide and polyvinyl alcohol to the mixture E, continue stirring for 10 to 15 minutes to obtain a mixture F, pass the mixture F through a membrane, cool and solidify in a nitrogen atmosphere with a purity of 99.99%, and obtain the composite material.
[0015] Furthermore, in S9.3, the curing temperature is 40° C. and the curing time is 24 to 48 hours.
[0016] In the formula of the present invention, polyurethane resin is used as the matrix material, and the polyurethane resin provides the main structural support of the composite material and has good thermal insulation performance. As a cross-linking agent, diphenylmethane diisocyanate reacts with the polyurethane resin to form a dense cross-linking network, thereby improving the mechanical strength and corrosion resistance of the composite material. The modified inorganic filler prepared by the present invention not only enhances the corrosion resistance of the composite material, but also improves its compatibility with the organic matrix, thereby further improving the overall performance of the composite material. Polyacrylamide is used as a dispersant to help the uniform distribution of various components in the composite material, thereby improving the uniformity and stability of the material. As a thickener, polyvinyl alcohol helps to adjust the viscosity of the composite material, thereby making it easier to operate during processing.
[0017] In the present invention, the hydroxyl group in the polyurethane resin reacts with the isocyanate group in diphenylmethane diisocyanate to form a carbamate bond, which is the main cross-linking reaction in the composite material. The reaction improves the mechanical strength and chemical corrosion resistance of the material; the inorganic components such as sodium silicate and zinc barium white in the modified inorganic filler further form hydrogen bonds or physical entanglements with the polyurethane resin and diphenylmethane diisocyanate, thereby further enhancing the compatibility and interface bonding force between the inorganic filler and the organic matrix.
[0018] The modified inorganic filler prepared by the present invention plays a vital role in improving the overall performance of the composite material. Sodium silicate is an inorganic binder, and its main function is to provide bonding between inorganic filler particles and enhance the overall strength of the filler. At the same time, the silicate ions produced by the hydrolysis of sodium silicate can form chemical bonds with a variety of metal ions, which helps to improve the corrosion resistance of the filler; zinc barium white, as an inorganic pigment and filler, not only has good hiding power and whiteness, but also can improve the weather resistance and chemical stability of the composite material. In the modified inorganic filler, zinc barium white is dispersed in the sodium silicate aqueous solution to form a stable suspension with sodium silicate, providing a uniform substrate for subsequent reactions; bismuth vanadate, as a high-performance inorganic material, has excellent corrosion resistance and thermal stability. In the modified inorganic filler, after bismuth vanadate is mixed and ground with monohydrate oxalic acid, its dispersibility and activity can be effectively improved, thereby enhancing the interfacial bonding force between the filler and the organic matrix; monohydrate oxalic acid, as a reducing agent and complexing agent, can form a complex with the metal ions in bismuth vanadate, which helps to uniformly disperse and improve the activity of bismuth vanadate. At the same time, oxalic acid monohydrate can decompose and produce gas during high-temperature roasting, which helps to form a porous structure and improve the thermal insulation performance of the filler; rock wool fiber, as a high-quality thermal insulation material, has excellent thermal insulation performance and chemical stability. In the modified inorganic filler of the present invention, rock wool fiber is mixed and ground with mixture C after soaking and drying, which can significantly improve the thermal insulation performance and mechanical strength of the filler.
[0019] In the preparation process of modified inorganic fillers, physical mixing and chemical bonding mainly occur between sodium silicate, lithopone, bismuth vanadate, oxalic acid monohydrate and rock wool fibers. The silicate ions produced by the hydrolysis of sodium silicate form chemical bonds with the metal ions in lithopone and bismuth vanadate, enhancing the binding force between filler particles. At the same time, oxalic acid monohydrate forms a complex with bismuth vanadate, which helps to evenly disperse bismuth vanadate. During the high-temperature roasting process, oxalic acid monohydrate decomposes to produce gas, forming a porous structure, and the chemical bonding between sodium silicate and metal ions is further consolidated to form a stable inorganic network structure; In addition, inorganic components such as sodium silicate, lithopone and bismuth vanadate in the modified inorganic filler can form hydrogen bonds or chemical bonds with functional groups such as hydroxyl and amino groups in the polyurethane resin, enhance the interfacial bonding between the filler and the organic matrix, and improve the overall strength and corrosion resistance of the composite material; after sodium silicate is dissolved in water, silicate ions will be formed. These silicate ions have certain activity and will interact with functional groups such as hydroxyl and amino groups in the polyurethane resin. On the one hand, silicate ions can bind to metal ions in the polyurethane resin through coordination bonds; on the other hand, oxygen atoms in silicate ions can also form hydrogen bonds with hydrogen atoms in the polyurethane resin, thereby enhancing the bonding between the inorganic filler and the resin. As an inorganic pigment, lithopone has certain polarity and activity on its surface. During the modification process, lithopone particles are coated with sodium silicate aqueous solution and homogenized to make the surface of lithopone particles more uniform and have a certain negative charge. These negative charges can be electrostatically attracted to the amino groups in the polyurethane resin, and the active sites on the surface of lithopone will also form chemical bonds with the functional groups in the polyurethane resin. The surface of bismuth vanadate has many active sites. During the modification process, bismuth vanadate is mixed and ground with monohydrate oxalic acid to make its surface rougher and expose more active sites. These active sites can react chemically with functional groups such as hydroxyl and amino groups in the polyurethane resin to form chemical bonds. At the same time, the bismuth ions and vanadium ions in bismuth vanadate will also coordinate with the functional groups in the polyurethane resin, further enhancing the binding force between the inorganic filler and the resin.
[0020] The present invention significantly improves the corrosion resistance and thermal insulation performance of the composite material by adding materials such as diphenylmethane diisocyanate, modified inorganic filler, polyacrylamide and polyvinyl alcohol during the preparation process of the composite material. These additives can enhance the chemical stability, heat resistance and mechanical strength of the material; cooling and curing in a nitrogen atmosphere with a purity of 99.99% can effectively prevent the composite material from being oxidized during the curing process, further improving the corrosion resistance and service life of the product; the composite material obtained by the preparation method has excellent corrosion resistance and thermal insulation performance, and is suitable for a variety of harsh environments.
[0021] The polyurethane resin in the present invention was purchased from Shenyang Elepox Chemical Co., Ltd. with a purity of 99%; the diphenylmethane diisocyanate in the present invention was purchased from Nantong Runfeng Petrochemical Co., Ltd. with a purity of 99%; the zinc barium white in the present invention was purchased from Shenyang Elepox Chemical Co., Ltd. with a purity of 98%; the bismuth vanadate in the present invention was purchased from Guangdong Qianjin Chemical Reagent Co., Ltd. with a purity of 99.9%; the polyacrylamide in the present invention was purchased from Hubei Kewode Chemical Co., Ltd. with a purity of 99.9%; the rock wool fiber in the present invention was purchased from Sichuan Pawoko Mineral Fiber Products Group Co., Ltd.
[0022] Beneficial effects of the present invention: The corrosion-resistant heat-insulating composite material provided by the present invention effectively improves the mechanical strength, corrosion resistance and heat-insulating performance of the composite material through a carefully designed modified inorganic filler preparation process. The inorganic components such as sodium silicate, zinc barium white, bismuth vanadate, monohydrate oxalic acid and rock wool fiber in the modified inorganic filler form a stable inorganic network structure through chemical bonding and physical mixing, thereby enhancing the interfacial bonding force between the filler and the organic matrix. At the same time, a tight cross-linking network is formed between the inorganic filler and the organic components such as polyurethane resin and diphenylmethane diisocyanate, further improving the overall performance of the composite material. In addition, the introduction of polyacrylamide and polyvinyl alcohol effectively improves the processing performance and stability of the composite material. DETAILED DESCRIPTION
[0023] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0024] Example 1 The corrosion-resistant thermal insulation composite material has the following formula: by weight: 100 parts of polyurethane resin, 40 parts of diphenylmethane diisocyanate, 30 parts of modified inorganic filler, 5 parts of polyacrylamide, and 2 parts of polyvinyl alcohol. The preparation method of the modified inorganic filler is as follows: S1.1: Sodium silicate is dissolved in deionized water to obtain a sodium silicate aqueous solution with a mass fraction of 30%, and lithopone is dispersed in the sodium silicate aqueous solution with a solid-liquid mass ratio of 1:1. The mixture is put into a homogenizer and homogenized at 5 MPa for 20 min to obtain a mixture A; S1.2: bismuth vanadate and oxalic acid monohydrate were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 400 r / min for 0.5 h to obtain a mixture B, wherein the particle size of the mixture B was 600 mesh; S1.3: Mix mixture B and mixture A in a mass ratio of 1:1, stir at a speed of 300 r / min for 0.5 h, heat from room temperature to 300 °C at a rate of 5 °C / min and roast for 2 h. After roasting, slowly cool to room temperature at a rate of 2 °C / min, crush and grind to obtain mixture C. The particle size of mixture C is 800 mesh. S1.4: Soak the rock wool fiber in deionized water at 70°C for 5 hours. After soaking, dry it at 110°C for 12 hours in a high-purity nitrogen atmosphere with a purity of 99.99% to obtain dry rock wool fiber. Mix the dried rock wool fiber and mixture C in a mass ratio of 1:1, put them into a ball mill for grinding, the grinding machine speed is 500r / min, the grinding time is 1 hour, and the modified inorganic filler is obtained after sufficient grinding. The particle size of the modified inorganic filler is 1000 mesh.
[0025] The composite material preparation method is as follows: S9.1: Heat the polyurethane to 170° C. to make the polyurethane molten, add diphenylmethane diisocyanate in proportion, mix and stir at a speed of 200 r / min for 20 min to obtain a mixture D; S9.2: Add the modified inorganic filler to the mixture D, increase the stirring speed to 300 r / min, and stir for 30 min to obtain a mixture E; S9.3: Add polyacrylamide and polyvinyl alcohol to mixture E, continue stirring for 15 minutes to obtain mixture F, pass mixture F through a membrane, cool and solidify in a nitrogen atmosphere with a purity of 99.99% at a curing temperature of 40° C. and a curing time of 48 hours to obtain the composite material.
[0026] Example 2 The corrosion-resistant thermal insulation composite material has the following formula: by weight, 80 parts of polyurethane resin, 30 parts of diphenylmethane diisocyanate, 20 parts of modified inorganic filler, 3 parts of polyacrylamide, and 1 part of polyvinyl alcohol. The preparation method of the modified inorganic filler is as follows: S1.1: Sodium silicate is dissolved in deionized water to obtain a sodium silicate aqueous solution with a mass fraction of 20%, and lithopone is dispersed in the sodium silicate aqueous solution with a solid-liquid mass ratio of 1:1. The mixture is put into a homogenizer and homogenized at 3 MPa for 30 min to obtain a mixture A; S1.2: bismuth vanadate and oxalic acid monohydrate were mixed in a mass ratio of 1:0.5, and ground in a ball mill at a speed of 400 r / min for 0.5 h to obtain a mixture B, wherein the particle size of the mixture B was 600 mesh; S1.3: Mixture B and mixture A in a mass ratio of 1:2, stir at a speed of 300 r / min for 0.5 h, heat from room temperature to 300 °C at a rate of 5 °C / min and roast for 2 h. After roasting, slowly cool to room temperature at a rate of 2 °C / min, crush and grind to obtain mixture C. The particle size of mixture C is 800 mesh. S1.4: Soak the rock wool fiber in deionized water at 70°C for 4 hours. After soaking, dry it at 110°C for 12 hours in a high-purity nitrogen atmosphere with a purity of 99.99% to obtain dry rock wool fiber. Mix the dried rock wool fiber and mixture C in a mass ratio of 1:1, put them into a ball mill for grinding, the grinding machine speed is 500r / min, the grinding time is 2 hours, and the modified inorganic filler is obtained after sufficient grinding. The particle size of the modified inorganic filler is 1000 mesh.
[0027] The composite material preparation method is as follows: S9.1: Heat the polyurethane to 165° C. to make the polyurethane molten, add diphenylmethane diisocyanate in proportion, mix and stir at a speed of 200 r / min for 10 min to obtain a mixture D; S9.2: Add the modified inorganic filler to the mixture D, increase the stirring speed to 300 r / min, and stir for 20 min to obtain a mixture E; S9.3: Add polyacrylamide and polyvinyl alcohol to the mixture E, continue stirring for 10 minutes to obtain a mixture F, pass the mixture F through a membrane, cool and solidify in a nitrogen atmosphere with a purity of 99.99% at a curing temperature of 40° C. and a curing time of 24 hours to obtain the composite material.
[0028] Example 3 The corrosion-resistant thermal insulation composite material has the following formula: by weight, 90 parts of polyurethane resin, 30 parts of diphenylmethane diisocyanate, 20 parts of modified inorganic filler, 3 parts of polyacrylamide, and 2 parts of polyvinyl alcohol. The preparation method of the modified inorganic filler is as follows: S1.1: Sodium silicate is dissolved in deionized water to obtain a sodium silicate aqueous solution with a mass fraction of 30%, and lithopone is dispersed in the sodium silicate aqueous solution with a solid-liquid mass ratio of 1:1. The mixture is put into a homogenizer and homogenized at 5 MPa for 30 min to obtain a mixture A; S1.2: bismuth vanadate and oxalic acid monohydrate were mixed in a mass ratio of 1:0.5, and ground in a ball mill at a speed of 400 r / min for 0.5 h to obtain a mixture B, wherein the particle size of the mixture B was 600 mesh; S1.3: Mix mixture B and mixture A in a mass ratio of 1:1, stir at a speed of 300 r / min for 0.5 h, heat from room temperature to 300 °C at a rate of 5 °C / min and roast for 2 h. After roasting, slowly cool to room temperature at a rate of 2 °C / min, crush and grind to obtain mixture C. The particle size of mixture C is 800 mesh. S1.4: Soak the rock wool fiber in deionized water at 70°C for 6 hours. After soaking, dry it at 110°C for 12 hours in a high-purity nitrogen atmosphere with a purity of 99.99% to obtain dry rock wool fiber. Mix the dried rock wool fiber and mixture C in a mass ratio of 1:1, put them into a ball mill for grinding, the grinding machine speed is 500r / min, the grinding time is 2 hours, and the modified inorganic filler is obtained after sufficient grinding. The particle size of the modified inorganic filler is 1000 mesh.
[0029] The composite material preparation method is as follows: S9.1: Heat the polyurethane to 175° C. to make the polyurethane molten, add diphenylmethane diisocyanate in proportion, mix and stir at a speed of 200 r / min for 20 min to obtain a mixture D; S9.2: Add the modified inorganic filler to the mixture D, increase the stirring speed to 300 r / min, and stir for 30 min to obtain a mixture E; S9.3: Add polyacrylamide and polyvinyl alcohol to mixture E, continue stirring for 15 minutes to obtain mixture F, pass mixture F through a membrane, cool and solidify in a nitrogen atmosphere with a purity of 99.99% at a curing temperature of 40° C. and a curing time of 48 hours to obtain the composite material.
[0030] Comparative Example 1 In this comparative example, no sodium silicate was added during the preparation of the modified inorganic filler, and the remaining steps were consistent with those in Example 1.
[0031] Comparative Example 2 In this comparative example, no lithopone was added during the preparation of the modified inorganic filler, and the remaining steps were consistent with those in Example 1.
[0032] Comparative Example 3 In this comparative example, bismuth vanadate and oxalic acid monohydrate were not added during the preparation of the modified inorganic filler, and the remaining steps were consistent with those in Example 1.
[0033] Comparative Example 4 In this comparative example, rock wool fiber was not added during the preparation of the modified inorganic filler, and the remaining steps were consistent with those in Example 1.
[0034] Comparative Example 5 In this comparative example, no diphenylmethane diisocyanate was added during the preparation of the composite material, and the remaining steps were consistent with those of Example 1.
[0035] The corrosion resistance and thermal conductivity of the embodiments and comparative examples were tested. Thermal conductivity is an important indicator for measuring the thermal insulation performance of thermal insulation materials. The smaller the thermal conductivity, the better the thermal insulation performance. The thermal conductivity determination in the present invention is carried out in reference to the standard GB / T25261-2018, and the corrosion resistance of the present invention is carried out in reference to the standard GB / T1771-2007. The experimental results are summarized in the following table.
[0036] It can be seen from the examples and comparative examples that the modified inorganic filler prepared in the present invention effectively improves the thermal insulation performance and corrosion resistance of the composite material, and the addition of diphenylmethane diisocyanate also effectively improves the performance of the composite material.
[0037] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A corrosion-resistant thermal insulation composite material, characterized in that: The corrosion-resistant thermal insulation composite material has the following formula: by weight, 80-100 parts of polyurethane resin, 30-40 parts of diphenylmethane diisocyanate, 20-30 parts of modified inorganic filler, 3-5 parts of polyacrylamide, and 1-2 parts of polyvinyl alcohol. The modified inorganic filler is prepared by mixing sodium silicate, lithopone, bismuth vanadate, a mixture of oxalic acid monohydrate and rock wool fiber.
2. The corrosion-resistant thermal insulation composite material according to claim 1, characterized in that: The specific preparation method of the modified inorganic filler is as follows: S1.1: Sodium silicate is dissolved in deionized water to obtain a sodium silicate aqueous solution with a mass fraction of 20-30%, and lithopone is dispersed in the sodium silicate aqueous solution with a solid-liquid mass ratio of 1:
1. The mixture is put into a homogenizer and homogenized at 3-5 MPa for 20-30 min to obtain a mixture A; S1.2: bismuth vanadate and oxalic acid monohydrate were mixed in a mass ratio of 1:(0.5-1), and ground in a ball mill at a speed of 400 r / min for 0.5 h to obtain a mixture B; S1.3: Mix mixture B and mixture A in a mass ratio of 1:(1-2), stir at a speed of 300 r / min for 0.5 h, heat from room temperature to 300 °C and roast for 2 h. After roasting, slowly cool to room temperature, crush and grind to obtain mixture C; S1.4: Soak the rock wool fiber in deionized water at 70°C for 4 to 6 hours. After soaking, dry it at 110°C for 12 hours in a high-purity nitrogen atmosphere with a purity of 99.99% to obtain dry rock wool fiber. Mix the dried rock wool fiber and mixture C in a mass ratio of 1:1, put them into a ball mill for grinding, and obtain the modified inorganic filler after sufficient grinding.
3. The corrosion-resistant thermal insulation composite material according to claim 2, characterized in that: The particle size of the mixture B in S1.2 is 600 mesh.
4. The corrosion-resistant thermal insulation composite material according to claim 2, characterized in that: The rate of heating from room temperature to 300°C in S1.3 is 5°C / min.
5. The corrosion-resistant thermal insulation composite material according to claim 2, characterized in that: The slow cooling rate in S1.3 is 2°C / min.
6. The corrosion-resistant thermal insulation composite material according to claim 2, characterized in that: The particle size of the mixture C in S1.3 is 800 mesh.
7. The corrosion-resistant thermal insulation composite material according to claim 2, characterized in that: The grinding machine speed in S1.4 is 500r / min, and the grinding time is 1-2h.
8. The corrosion-resistant thermal insulation composite material according to claim 2, characterized in that: The particle size of the modified inorganic filler obtained by grinding in S1.4 is 1000 mesh.
9. A method for preparing a corrosion-resistant thermal insulation composite material, based on the corrosion-resistant thermal insulation composite material according to any one of claims 1 to 8, characterized in that: The composite material preparation method is as follows: S9.1: Heat the polyurethane to 165-175°C to make the polyurethane molten, add diphenylmethane diisocyanate in proportion, mix and stir at a speed of 200 r / min for 10-20 min to obtain a mixture D; S9.2: Add the modified inorganic filler to the mixture D, increase the stirring speed to 300 r / min, and stir for 20 to 30 min to obtain a mixture E; S9.3: Add polyacrylamide and polyvinyl alcohol to the mixture E, continue stirring for 10 to 15 minutes to obtain a mixture F, pass the mixture F through a membrane, cool and solidify in a nitrogen atmosphere with a purity of 99.99%, and obtain the composite material.
10. The method for preparing a corrosion-resistant thermal insulation composite material according to claim 9, characterized in that: In the S9.3, the curing temperature is 40° C. and the curing time is 24 to 48 hours.
Citation Information
Patent Citations
Isocyanate-containing thermoplastic polyurethane
CN101198648A
Thermoplastic polyurethane composition for slush molding and preparation method thereof
CN107746565A
Low-temperature reaction type polyurethane composite thermal insulation material and preparation method thereof
CN115505090A
Wear-resistant and corrosion-resistant coating for pipeline and preparation method thereof
CN119410248A
new insulating material and process for its preparation
FR1378191A